2010
DOI: 10.2138/am.2010.3358
|View full text |Cite
|
Sign up to set email alerts
|

IR absorption coefficients for water in nominally anhydrous high-pressure minerals

Abstract: Infrared spectroscopic quantification of traces of OH and H 2 O in minerals and glasses is based on the Beer Lambert law A = ε·c·t, where ε is the molar absorption coefficient. Numerous experimental and theoretical studies show that ε generally increases with decreasing wavenumbers. However, this general trend seems to be valid only for hydrous minerals and glasses and should not be applied to water quantification in nominally anhydrous minerals (NAMs) that incorporate traces of water in their structures. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Two or three spectra for each crystal were obtained on the polished surfaces, and one or two crystals from each run were analyzed. After background and baseline subtraction, the water contents were determined from the FT-IR spectra using the Beer-Lambert law of the formCnormalH2normalO=true3italicAfalse(normalυfalse)MnormalH2normalOεinormalτnormalρitalicdnormalυwhere C H2O is the water content in wt ppm, and A (ν) is the infrared absorption at wave number ν. M H2O is the molar weight of water (18.02 g/mol); ε i is the absorption coefficient [98,600 liter∙mol −1 ∙cm −2 for ringwoodite ( 37 )]; τ is the sample thickness, which is normalized to 1 cm; and ρ is the density (3900 g/liter). The integration was performed for the wave number range 3740 to 2600 cm −1 ( 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Two or three spectra for each crystal were obtained on the polished surfaces, and one or two crystals from each run were analyzed. After background and baseline subtraction, the water contents were determined from the FT-IR spectra using the Beer-Lambert law of the formCnormalH2normalO=true3italicAfalse(normalυfalse)MnormalH2normalOεinormalτnormalρitalicdnormalυwhere C H2O is the water content in wt ppm, and A (ν) is the infrared absorption at wave number ν. M H2O is the molar weight of water (18.02 g/mol); ε i is the absorption coefficient [98,600 liter∙mol −1 ∙cm −2 for ringwoodite ( 37 )]; τ is the sample thickness, which is normalized to 1 cm; and ρ is the density (3900 g/liter). The integration was performed for the wave number range 3740 to 2600 cm −1 ( 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been shown that these values should not be applied to water quantification in nominally anhydrous minerals (NAMs); NAMs need mineral-specific ε−values (e.g. Rossman 2006, Koch-Müller and Rhede, 2010. Therefore, absorption coefficients (ε) were taken from Deon et al (2009) (2010) 75,300± 7,000 L mol H 2 O cm -2 for ol and ring, respectively.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…1) were synthesized in a multianvil apparatus and characterized by electron microprobe analyses (EMPA) and secondary ion mass spectrometry (SIMS). Details of the experimental procedures and results of EMPA are given in Taran et al (2009) and Koch-Müller et al (2009); details of the SIMS measurements are given in Koch-Müller and Rhede (2010).…”
Section: Sample Characterizationmentioning
confidence: 99%